Auto-amputated Ovarian Cyst with Compression Sequelae: A Case Report - Bilal Mirza (EL-Med-Pub, 2012)
Ovarian  cysts  contribute  a  major  share  of  cystic  lesions in  fetal  life. Quite often, these cysts are benign and resolve spontaneously. Occasionally, these cysts can twist, resulting in ovarian loss. We report a case of auto-amputated ovarian cyst presetting with intestinal obstruction.